Characterization of superconducting BSCCO/CaSiO3 and BSCCO/CaZrO3 Ag PIT wires - Nogueira, Natacha Andréia [UNESP] (2014)
The addition of two compounds, calcium silicate and calcium zirconate was tested in the preparation of Bi: 2212 silver sheathed wires by powder-in-tube method. The wires were treated in an atmosphere of O-2/Ar using partial melting method. The characterizations were structural and on their electrical and magnetic properties. It was found that the addition of calcium silicate or zirconate promoted higher transition temperatures, up to 116 K for BSCCO with 1wt.% CaSiO3. The critical current densities determined by transport and magnetization measurements were improved in comparison with the wires without any addition.